The Effect of BookTok Content Access Intensity on the Digital Literacy of Students in the Library and Information Science Study Program - Putri Monika; Marlini Marlini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study is motivated by the gap between the high intensity of social media use and the suboptimal level of students’ digital literacy, particularly in responding to BookTok content on TikTok, which is characterized by brevity, emotional appeal, and algorithm-driven exposure. This study aims to examine and describe the influence of BookTok content access intensity on the digital literacy of students in the Library and Information Science Program at Universitas Negeri Padang. A quantitative approach with an associative method was employed. The population consisted of 100 students from the 2022 cohort, from which 55 respondents were selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed through normality and linearity tests, Pearson correlation, simple linear regression, and coefficient of determination using SPSS. The findings reveal that the intensity of accessing BookTok content has a significant effect on students’ digital literacy (p < .05), with a correlation coefficient of 0.713, indicating a strong relationship. The coefficient of determination of 0.508 shows that 50.8% of the variance in digital literacy is explained by BookTok access intensity, while the remaining 49.2% is influenced by other factors. Overall, both access intensity and digital literacy were categorized as good. These findings indicate that higher intensity of BookTok content access corresponds to higher levels of digital literacy among students. This study contributes to the literature on digital literacy and social media-based learning by demonstrating the role of algorithm-driven book-related content in shaping students’ digital competencies. Practically, the findings highlight the importance of critical and strategic engagement with social media and support the integration of social media-based digital literacy development within higher education contexts.